Link between cultural dimensions and leadership styles of organizational managers in Turkey context of hofstede and GLOBE studies - Cuhadar, Sevinur; Rudnák, Ildikó (Studia Mundi – Economica, 2022)
This research aimed to provide a better comprehension of link between cultural dimensions and leadership styles of managers in Turkey based on previous studies in the literature which draws on both international and Turkish research. We have done this by clarifying concept of cross-cultural leadership, cross-cultural studies related to cultural dimensions, cultural dimensions of Turkey and leadership styles of Turkish managers. Organizational leadership is affected by many factors such as cultural dimensions. Cultural dimensions have impact on leadership styles of managers and many scholars have studied on link between leadership style of managers and cultural dimensions of countries. Based on literature, it is proved positive relationship between two components that cultural dimensions and leadership styles of Turkish managers.Turkey is collectivist,high power distance and human-oriented country, therefore Paternalistic and Authoritarian leadership style are the most common among the managers